2019
DOI: 10.1177/1094670519838623
|View full text |Cite
|
Sign up to set email alerts
|

When and Why a Squeakier Wheel Gets More Grease: The Influence of Cultural Values and Anger Intensity on Customer Compensation

Abstract: When customers express anger, do they gain greater returns, as suggested by the proverb “the squeaky wheel gets the grease”? If so, does the intensity of the squeak matter? In four studies, we explore employee compensation responses to customers who express relatively high- versus low-intensity anger in service-failure settings. The studies demonstrate that the cultural value of power distance (PD) moderates the relationship between emotional intensity and customer compensation: High-PD service employees offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 108 publications
(190 reference statements)
0
41
0
1
Order By: Relevance
“…Another cultural value found to affect assessments of inappropriateness is power distance-i.e., one's acceptance for power inequalities and social hierarchies (Hofstede, 2001). Glikson et al (2019) mentioned above, found that displays of high-intensity anger by customers were perceived as less appropriate by service providers (the target of the anger) who scored low (vs. high) in power distance. This led to lower amounts of compensation for the angry customer.…”
Section: Characteristics Of the Contextmentioning
confidence: 94%
See 4 more Smart Citations
“…Another cultural value found to affect assessments of inappropriateness is power distance-i.e., one's acceptance for power inequalities and social hierarchies (Hofstede, 2001). Glikson et al (2019) mentioned above, found that displays of high-intensity anger by customers were perceived as less appropriate by service providers (the target of the anger) who scored low (vs. high) in power distance. This led to lower amounts of compensation for the angry customer.…”
Section: Characteristics Of the Contextmentioning
confidence: 94%
“…Adam and Brett (2018) found a curvilinear relationship between anger intensity and negotiation outcomes, where concessions from the opposing side rose when moderate anger was expressed, but then fell again when the anger grew in intensity (and was in consequence perceived as less appropriate). Glikson et al (2019) found that customers' angry complaints yielded different results based on the intensity with which the anger was displayed. High-intensity anger was seen as both less appropriate and as more threatening than anger of lower intensity.…”
Section: Intensitymentioning
confidence: 99%
See 3 more Smart Citations